2017
DOI: 10.3389/fmicb.2017.01464
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Bacterial Communities of Trypanosome-Infected and Uninfected Glossina palpalis palpalis from Three Human African Trypanomiasis Foci in Cameroon

Abstract: Glossina sp. the tsetse fly that transmits trypanosomes causing the Human or the Animal African Trypanosomiasis (HAT or AAT) can harbor symbiotic bacteria that are known to play a crucial role in the fly's vector competence. We hypothesized that other bacteria could be present, and that some of them could also influence the fly's vector competence. In this context the objectives of our work were: (a) to characterize the bacteria that compose the G. palpalis palpalis midgut bacteriome, (b) to evidence possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 93 publications
(137 reference statements)
5
20
0
Order By: Relevance
“…Therefore, the two foci may share the same eco-climatic features with a Guinean-like climate characteristic of the Congo Basin’s forests. These results are also in agreement with Jacob et al [31], who demonstrated that the bacterial composition of flies collected at the Campo and Bipindi foci were not significantly different. In addition, this result is similar to that of Tchioffo et al [36] and Gimonneau et al [33] who did not show any significant differences between the bacterial flora of the mosquitoes Anopheles coluzzi and Anopheles gambiae in Cameroon.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, the two foci may share the same eco-climatic features with a Guinean-like climate characteristic of the Congo Basin’s forests. These results are also in agreement with Jacob et al [31], who demonstrated that the bacterial composition of flies collected at the Campo and Bipindi foci were not significantly different. In addition, this result is similar to that of Tchioffo et al [36] and Gimonneau et al [33] who did not show any significant differences between the bacterial flora of the mosquitoes Anopheles coluzzi and Anopheles gambiae in Cameroon.…”
Section: Discussionsupporting
confidence: 93%
“…This could be due to the fact that it has a more general tropism beyond the intestine and thus can be localized in several other tissues, both extracellularly and intracellularly, including the salivary glands and the hemocoel [38]. However, Sodalis has never been observed to be very abundant in tsetse fly midguts, with maximum reported abundances of around 0.26% [29] and 0.06% [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impacts of viral pathology on the tsetse symbionts determined. [ 42 , 47 , 53 , 58 , 59 , 148 172 ]; ([ 44 , 54 , 72 , 93 , 173 , 174 ]) (iii). Determine effects of radiation in tsetse, its microbiota and pathogens.…”
Section: Major Objective Of the Crpmentioning
confidence: 99%
“…One of the major achievements of this CRP is the discovery of Spiroplasma as a fourth endosymbiont (in addition to Wigglesworthia , Sodalis , and Wolbachia ) in some wild and laboratory-reared tsetse populations [ 58 , 59 ]. While the function of this bacterium in tsetse is currently unknown, it likely to impact colony fitness.…”
Section: Current Status and Achievementsmentioning
confidence: 99%